Novel Riboflavin-Inspired Conjugated Bio-Organic Semiconductors - Richtar, Jan; Heinrichova, Patricie; Apaydin, Dogukan Hazar; Schmiedova, Veronika; Yumusak, Cigdem; Kovalenko, Alexander; Weiter, Martin; Sariciftci, Niyazi Serdar; Krajcovic, Jozef (Molecules (Basel, Switzerland), 2018)
Flavins are known to be extremely versatile, thus enabling routes to innumerable modifications in order to obtain desired properties. Thus, in the present paper, the group of bio-inspired conjugated materials based on the alloxazine core is synthetized using two efficient novel synthetic approaches providing relatively high reaction yields. The comprehensive characterization of the materials, in order to evaluate the properties and application potential, has shown that the modification of the initial alloxazine core with aromatic substituents allows fine tuning of the optical bandgap, position of electronic orbitals, absorption and emission properties. Interestingly, the compounds possess multichromophoric behavior, which is assumed to be the results of an intramolecular proton transfer.
Keywords: flavins; Models, Molecular; Electrochemistry; Riboflavin; elektrochemie; Spectrophotometry, Ultraviolet; polovodiče; flaviny; molekulární modely; oxygen evolution; molekulární struktura; Molecular Structure; biomimetické materiály; biomimetic energy storage; Biomimetics; biomimetika; spektrofotometrie ultrafialová; Semiconductors; Biomimetic Materials; conjugated materials; bio-inspired material; Flavins; riboflavin